2012
DOI: 10.1016/j.jvs.2011.11.062
|View full text |Cite|
|
Sign up to set email alerts
|

Repetitive progressive thermal preconditioning hinders thrombosis by reinforcing phosphatidylinositol 3-kinase/Akt-dependent heat-shock protein/endothelial nitric oxide synthase signaling

Abstract: Repetitive PTP is better than single PTP to hinder thrombosis formation via reinforcing PI3K/Akt-dependent Hsp70/eNOS signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…Recent studies have showed that PI3K/AKT signal pathway was involved in the induction of HSP70 expression [29,30]. This regulation might rely on the fact that the activation of AKT inhibited GSK-3β [31], and the inhibition of GSK-3β could activate HSF1.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have showed that PI3K/AKT signal pathway was involved in the induction of HSP70 expression [29,30]. This regulation might rely on the fact that the activation of AKT inhibited GSK-3β [31], and the inhibition of GSK-3β could activate HSF1.…”
Section: Discussionmentioning
confidence: 99%
“…Membranes were then incubated for 1 h at room temperature with anti-rabbit or rabbit anti-sheep IgG antibodies conjugated to horseradish peroxidase (Vector Laboratories, Burlingame, CA, USA), and proteins were visualized using a commercial enhanced chemiluminescence kit (GE Healthcare). Band densities were determined semi-quantitatively by densitometry using an Alpha Innotech image analysis system (San Leandro, CA, USA) [ 50 ].…”
Section: Methodsmentioning
confidence: 99%
“…Elevated H 2 O 2 in the impaired arteriovenous fistulas from chronic kidney diseases animals or cell death caused a significant decrease in p-Akt levels and an activated Bax/caspase-3 signaling (7,14). Activation of PI3K/Akt signaling and subsequent enhancement of eNOS, phospho-Ser473-Akt, and phospho-Ser1177-eNOS by several treatments increases NO production, and reduces vascular ROS, oxidative stress, and ICAM-1 expression in the damaged tissue (7,18). Our study also found that the decreased p-Akt/p-eNOS/NO signaling by I/R injury is associated with the reduction of renal microcirculation, the increase of renal H 2 O 2 amount BUN, autophagy and apoptosis consequently leading to proximal tubular injury by the elevation of urinary GST level.…”
Section: Discussionmentioning
confidence: 99%
“…In the endothelial cells, the production of H 2 O 2 , an endothelium-dependent contracting factor, through NAD(P)H oxidase activation causes smooth muscle contraction in the rat renal artery (10). Several preconditioning methods require phosphatidylinositol 3-kinase (PI3K)/Akt signaling for enhancing endothelial nitric oxide synthase (eNOS) expressions, phosphorylation of eNOS (p-eNOS) at Ser-1177, and nitric oxide (NO) production to afford cardiovascular protection (14,18,31). However, H 2 O 2 downregulates PI3K/Akt signaling, p-eNOS expression and NO level and leads to oxidative injury and thrombosis (7,14).…”
Section: Introductionmentioning
confidence: 99%